Penyelesaian Sengketa Terhadap Badan Penyelenggara Jaminan Sosial Ketenagakerjaan Dinas Pemadam Kebakaran Berdasarkan Undang-Undang 24 Tahun 2011 Tentang Badan Penyelenggara Jaminan Sosial - Edo Setiawan Saputra; Herfian Ageng Pangestu; Ardiansyah; Norega (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2026)
Public demand for security and protection continues to increase along with growing social, economic, health, and occupational risks. Insurance serves as an important instrument for transferring risk to another party through a protection mechanism, including conventional insurance, sharia insurance, and life insurance. In the employment context, social protection plays a crucial role in maintaining workers’ welfare, improving work motivation, and supporting national productivity. The enactment of Law Number 24 of 2011 concerning the Social Security Administering Body marked an institutional transformation in Indonesia’s social security system, including the conversion of Askes into BPJS Kesehatan and Jamsostek into BPJS Ketenagakerjaan. This protection is particularly important for employees of the Palembang City Fire Department because firefighting work carries high risks to safety, health, and life. However, the implementation of social security programs may also create disputes among participants, employers, BPJS, and the government. Therefore, a clear legal mechanism is needed to prevent and resolve disputes effectively, either through litigation or non-litigation procedures. This study emphasizes that social security does not merely function as administrative protection, but also as a legal instrument to guarantee workers’ rights, improve welfare, and provide legal certainty for workers in high-risk occupations.